2013
DOI: 10.1103/physrevb.88.054501
|View full text |Cite
|
Sign up to set email alerts
|

Possible nematic order driven by magnetic fluctuations in iron pnictides

Abstract: In this paper, instabilities of the isotropic metallic phase in iron pnictides are investigated. The relevant quartic fermionic interaction terms in the model are identified using phase space arguments. Using the functional integral formalism, a Hubbard-Stratonovich transformation is used to decouple these quartic terms. This procedure introduces several bosonic fields which describe the low-energy collective modes of the system. By studying the behavior of these collective modes, a possible instability is fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This intrinsic splitting arises because of the effect of the non trivial yz/zx C 4 symmetry at low energy. This mechanism is different from breaking explicitly the yz/zx symmetry by introducing a small crystal field in the Hamiltonian 38,44 or from inferring it assuming X-Y pocket interaction 71 . Our analysis clearly reveals the intrinsic interrelation between spin and orbital d.o.f.…”
Section: Effective Action For the Multiorbital Systemmentioning
confidence: 99%
“…This intrinsic splitting arises because of the effect of the non trivial yz/zx C 4 symmetry at low energy. This mechanism is different from breaking explicitly the yz/zx symmetry by introducing a small crystal field in the Hamiltonian 38,44 or from inferring it assuming X-Y pocket interaction 71 . Our analysis clearly reveals the intrinsic interrelation between spin and orbital d.o.f.…”
Section: Effective Action For the Multiorbital Systemmentioning
confidence: 99%
“…Furthermore, the tetragonal phase above T S turns out to be unconventional: various electronic properties have been found to break the fourfold symmetry of the Fe-As planes . [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The relative role and the microscopic origin of the spin and orbital instabilities leading to such an "electronic nematic state" are also controversial. 23,[26][27][28][29][30][31][32][33][34][35][36][37] Actually, because magnetic and orbital degrees of freedom are entangled and most likely cooperate, 38 it is challenging to determine which one, if any, is dominant.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The relative role and the microscopic origin of the spin and orbital instabilities leading to such an "electronic nematic state" are also controversial. 23,[26][27][28][29][30][31][32][33][34][35][36][37] Actually, because magnetic and orbital degrees of freedom are entangled and most likely cooperate, 38 it is challenging to determine which one, if any, is dominant. While both the magnetic and orbital scenarios find support in experiments , 3,5,6,14,20,[39][40][41][42][43] the nematic state remains puzzling.…”
mentioning
confidence: 99%
“…According to the former scenario, Z 2 spin-nematic order can induce the orthorhombic lattice distortion as well as ferro-orbital order involving d xz and d yz orbitals although only with a small splitting between the orbitals. [12][13][14] On the other hand, several studies have suggested a principle role for the orbital degree of freedom. [15][16][17][18][19] Whereas the need to include both the spin-lattice as well as the orbital-lattice coupling has been stressed in a Monte Carlo study within a three orbital spin-fermion model.…”
Section: Introductionmentioning
confidence: 99%